PENINGKATAN HASIL BELAJAR SISWA MATERI KONSEP DASAR ILMU EKONOMI MELALUI MODEL DESCOVERY LEARNING BERORIENTASI KEARIFAN LOKAL THK KELAS X - Wapa, Andi; Suastika, I Nengah; Lasmawan, I Wayan (STKIP Persada Khatulistiwa Sintang, 2023)
This research is based on problems regarding economics subjects in classes that are still below the KKM, so this research aims to improve the learning outcomes of class X students in economics subjects at MA Nurul Iman by using a discovery learning model oriented to THK local wisdom. The method used was Classroom Action Research with a research sample of 30 MA Nurul Iman Rowokangkung Lumajang students with data collection based on two treatment cycles. Data analysis in this study refers to the indicator of achievement of subject competency, namely 75. The results of applying this method show an increase in learning outcomes based on the pre-cycle of 74.50, then in the first cycle 80.83 and in the second cycle 89.00, meaning that the learning model increases learning outcomes with a percentage of completeness. learning outcomes rose from 30% to 67% in the first cycle then rose again to 87% in the second cycle. Suggestions for teachers should always pay attention to students' learning readiness factors so that it is easy to provide learning. Next, use a cooperative model to make learning more collaborative, and use local wisdom that supports learning so that it can be preserved